Dental experiences related to oral care of children with autism spectrum disorders in Saudi Arabia: A literature review - Jehan AlHumaid (Saudi Dental Journal)
The burden of autism spectrum disorder (ASD) in Saudi Arabia remains unclear with a dearth of literature, which focus on risk factors, prevalence, or interventions. This study is a review of the published literature related to dental experiences of children with ASD in Saudi Arabia. Twenty-two studies were included in this review, based on the predefined inclusion criteria which examined dental disease prevalence in children with ASD, identified the risk factors and the potential barriers to oral care. Results uncovered a lack of systematically published studies from Saudi Arabia which might have led to the limited development of effective oral health policies in the Kingdom. Identification of research gaps and potential intervention policies are needed to improve the oral health and quality of life of children with ASD in Saudi Arabia.